The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14338/ijpt-18-00010.1
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Studies for the Development of Particle Therapy

Abstract: Proton therapy for cancer is now in widespread use, and facilities for carbon ion therapy are showing great promise, but a more complete understanding of the mechanisms underlying particle radiation therapy is still needed in order to optimize treatment. Studies of gene expression, especially those using whole genome techniques, can provide insight into many of the questions still remaining, from the molecular mechanisms involved to predicting patient outcome. This review will summarize gene expression studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Even though we also found several genes “unique” to a specific radiation type, it is likely that many of them would also respond to the other radiation types in a different experimental set-up (i.e. time-dose combination) due to the differences in RBE and\or gene expression kinetics, but what is already clear from our and other studies is that the magnitude of gene expression changes and the number of differentially expressed genes are consistently higher for high-LET particles ( 22 ). Some of the observed differences may be explained by the different nature of X-rays (photons) and heavy ions (particles).…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…Even though we also found several genes “unique” to a specific radiation type, it is likely that many of them would also respond to the other radiation types in a different experimental set-up (i.e. time-dose combination) due to the differences in RBE and\or gene expression kinetics, but what is already clear from our and other studies is that the magnitude of gene expression changes and the number of differentially expressed genes are consistently higher for high-LET particles ( 22 ). Some of the observed differences may be explained by the different nature of X-rays (photons) and heavy ions (particles).…”
Section: Discussionmentioning
confidence: 70%
“…Radiobiological transcriptional studies can offer valuable insight in this regard, revealing the biological basis of the cellular response to different radiation types ( 21 , 22 ). Peripheral blood is an easily-accessible biological sample which allows minimally invasive testing.…”
Section: Introductionmentioning
confidence: 99%
“…Authors showed that results are strongly influenced by the type of cells, culture condition, dose, dose rate, fractionation, and other physical features (i.e., LET, RBE) [22]. S.A. Amundson et al published that proton irradiation compared to X or gamma irradiation increases gene expression level in both their number and strength of response [23]. In the case of rat C6 glioblastoma, similar to human glioblastomas grade IV, the significant decrease in proliferation was found at a dose of 5 Gy and 10 Gy of X-rays after 48 h of culture [24].…”
Section: Resultsmentioning
confidence: 99%
“…Transcriptional profiling corresponds to the genes induced at these different dose levels. In general, at low doses, the genes induced are involved in general metabolism (bioenergetics and biosynthetic functions) whereas high doses activate genes involved in cell cycle arrest, DNA repair and apoptosis [ 182 , 183 ]. Even if these are not yet fully understood, they may well have a bearing on radioprotection and radiotherapeutic issues.…”
Section: Ionizing Radiation (Ir) Effects Involving Mitochondriamentioning
confidence: 99%